Investigating bacterial diversity involved in the production of vegetable-based ethnic fermented food of North Bengal and their metabolic pathways with reverse ecology approach - Ghatani, Kriti; Sha, Shankar Prasad; Thapa, Subarna; Sarkar, Indrani; Sen, Gargi; Sen, Arnab (Frontiers in Sustainable Food Systems, 2024)
Endemic fermented vegetables play a crucial role in local cuisine and culture, with traditionally fermented raw green vegetables like gundruk being a popular practice in North Bengal and Sikkim, India. However, there's a gap in the microbial profiling of these vegetables. This study aimed to explore the diversity of dominant bacterial populations in fermented leafy vegetables using both culture-dependent and independent methods.In addition to isolating bacteria using conventional methods, we conducted phenotypic and biochemical characterization, community DNA isolation, and amplicon sequencing. We also introduced a new approach in bioinformatics analysis: Reverse Ecology, which analyzes complementation and competition among participant microbes. In conventional culturedependent techniques, LAB genera such as Lactobacillus, Enterococcus, Leuconostoc, andPediococcus have been identified as predominant consortia whereas, Metagenomic analysis revealed that the microbiome of fermented dried leafy vegetables was mainly composed of Firmicutes, Proteobacteria, Actinobacteria, Bacteroides, and Planctomycetes at the phylum level.